Efficient Algorithms for Constructing Preset Distinguishing Sequences for Nondeterministic Finite State Machines - Haddad, Abdul Rahim (2016)
A Master of Science thesis in Computer Engineering by Abdul Rahim Haddad entitled, "Efficient Algorithms for Constructing Preset Distinguishing Sequences for Nondeterministic Finite State Machines," submitted in June 2016. Thesis advisor is Dr. Khaled El-Fakih and thesis co-advisor is Dr. Gerassimos Barlas. Soft and hard copy available.